Development and Implementation of Jobsheets in Basic Culinary Competence - S, Salam Sofan; Sutopo, Yeri; Kusumawardani, Rini (Universitas Negeri Semarang, 2024)
Vocational education is developed based on societal needs and challenges. To enhance competencies, vocational training is necessary to provide students with real-world experiences. The aim of this research is to develop jobsheets, test their feasibility and practicality, and analyze the improvement in basic culinary skills among students using the jobsheets. This research employs the ADDIE model of Research and Development (RnD), which consists of five development stages: analysis, design, development, implementation, and evaluation. The subjects of this study were 36 tenth-grade culinary students at SMK N 6 Kota Semarang. The data analysis used t-tests to examine how the use of jobsheets impacts basic culinary skills. The research results indicate that (1) the jobsheets are feasible and practical for use in practical learning, (2) the jobsheets effectively improve cognitive, affective, and psychomotor aspects in basic culinary skills, and (3) the achievement of basic culinary competencies is also influenced by motivational and environmental factors.